Application of molecularly imprinted polymers in food sample analysis – a perspective - Lok, Chui Mei; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Since the introduction of the molecularly imprinting technology (MIT) in 1970s, it becomes an emerging technology with the potential for wide-ranging applications in food manufacturing, processing, analysis and quality control. It has been successfully applied in food microbiology, removal of undesirable components from food matrices, detection of hazardous residues or pollutants and sensors. Molecularly imprinted solid-phase extraction (MISPE) is the most common application so far. The review describes the methods of making the molecularly imprinted polymer systems, the application of the technology in food safety issues and the remaining challenges.